2019
DOI: 10.3390/brainsci9120342
|View full text |Cite
|
Sign up to set email alerts
|

Paternal—but Not Maternal—Autistic Traits Predict Frontal EEG Alpha Asymmetry in Infants with Later Symptoms of Autism

Abstract: Previous research found that the parental autism phenotype is associated with child autism spectrum disorder (ASD), even if the pathway between autistic traits in parents and child ASD is still largely unknown. Several studies investigated frontal asymmetry in alpha oscillation (FAA) as an early marker for ASD. However, no study has examined the mediational effect of FAA between parental autistic traits and child ASD symptoms in the general population. We carried out a prospective study of 103 typically develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…First of all, infants at risk to develop BAP by having a parent with sub-threshold high autistic traits share common alterations in low-level cognitive processes with infant siblings of ASD children (e.g. visual attention, Ronconi et al 2014 ; alpha-band brain oscillations, Riva et al 2019 ; visual SL, our study), suggesting that the BAP approach is crucial since infancy to evaluate the presence of endophenotypes related to ASD symptoms. Moreover, autistic traits can be evaluated in the general population giving the possibility to understand the functioning of the autistic phenotype with many more participants than in most studies with ASD children or infants at risk for ASD.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…First of all, infants at risk to develop BAP by having a parent with sub-threshold high autistic traits share common alterations in low-level cognitive processes with infant siblings of ASD children (e.g. visual attention, Ronconi et al 2014 ; alpha-band brain oscillations, Riva et al 2019 ; visual SL, our study), suggesting that the BAP approach is crucial since infancy to evaluate the presence of endophenotypes related to ASD symptoms. Moreover, autistic traits can be evaluated in the general population giving the possibility to understand the functioning of the autistic phenotype with many more participants than in most studies with ASD children or infants at risk for ASD.…”
Section: Discussionmentioning
confidence: 65%
“…Autistic traits are continuously distributed in the general population, representing the so-called Broader Autism Phenotype (BAP), and are heritable, with heritability rates ranging from 36.0% to 87.0% (Robinson et al 2011 ; Ronald and Hoekstra 2011 ). It has been recently shown that autistic traits in parents are associated with both the clinical and subclinical behavioral autistic phenotype of offspring (De la Marche et al 2015 ; Gerdts and Bernier 2011 ; Jones et al 2017 ; Levin-Decanini et al 2013 ; Maxwell et al 2013 ; Riva et al 2019 ; Schwichtenberg et al 2010 ). For example, the incidence of high autistic traits in ASD parents ranges from 2.6% to 80.0% (see review by Rubenstein and Chawla 2018 ), and autistic traits in ASD parents are associated with the severity of ASD symptoms in children (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The study sample was recruited within an ongoing longitudinal project aiming at identifying early risk markers for NDD. Specifically, the longitudinal study included children from the general population [40,41] and children with a first-degree relative (i.e., a sibling) with a clinical diagnosis of ASD, DLD or Learning Disabilities [42,43].…”
Section: Methodsmentioning
confidence: 99%